PENGARUH SERBUK DAUN RIMAU (Toona sinensis Roem.) TERHADAP KEMATIAN LARVA ULAT GRAYAK (Spodoptera litura F.) - Rizal, Syamsul (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2014)
Research to determine the effect of leaf powder Rimau (Toona sinensis Roem.) To death army worm larvae (Spodoptera litura F.) was conducted in August 2013 at the Forestry Research InstituteÂ Palembang. The results shows Rimau leaf powder can cause death armyworm larvae and relatively less toxic. Key words: leaf powder Rimau, army worm larvae